1982
DOI: 10.1002/j.1556-6978.1982.tb01693.x
|View full text |Cite
|
Sign up to set email alerts
|

Research Activity and Scholarly Productivity Among Counselor Educators

Abstract: This study investigated research and scholarly activities among a group of randomly selected counselor educators and found “high” and “low” producers to be distinguishable along the following dimensions: years in the present career, preferred professional activity, sex, academic rank, kind of institutional affiliation (college or university), institutional size, when the first publication was produced, number of journal subscriptions, average weekly time devoted to research, and whether or not the counselor ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

1983
1983
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Ten men were listed as authors of 53 articles; three women were listed as authors of 13 articles. Walton (1982) surveyed 520 persons listed in the 1979 ACES roster and received 255 replies (56.1%). Entries in the Social Sciences Citation Index included references for 189 men and 66 women.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ten men were listed as authors of 53 articles; three women were listed as authors of 13 articles. Walton (1982) surveyed 520 persons listed in the 1979 ACES roster and received 255 replies (56.1%). Entries in the Social Sciences Citation Index included references for 189 men and 66 women.…”
mentioning
confidence: 99%
“…Entries in the Social Sciences Citation Index included references for 189 men and 66 women. Walton (1982) concluded that more men than women were high producers.…”
mentioning
confidence: 99%
“…In order to begin correcting this situation, we need to focus attention on the training of future doctoral level professionals who comprise the pool of potential researchers. Results from Walton's (1982) recent study of scholarly productivity of counselor educators indicates the carry-over effect of early interest and involvement in research.…”
mentioning
confidence: 99%
“…In spite of these difficulties, individuals who develop skills and interests in research and find themselves in settings where research is encouraged or expected are faced with another set of problems. In higher education, professors often find themselves without the necessary assistance required to engage in the range and volume of activities that commonly occur between the inception of an idea and final report writing (Walton, 1982). This is especially true in the development of programmatic research studies, because systematic inquiry efforts can require relatively large-scale resources that are hard to develop and maintain.…”
mentioning
confidence: 99%
“…It is extremely important that counselors leave graduate training knowing how to counsel, and their coursework should support that primary goal. Still, several authors have indicated with concern that the number of individuals conducting and publishing research is less than sufficient (Gelso, 1979;Gelso, Raphael, Black, Rardin, & Skalkos, 1983;Holland, 1982;Stockton & Hulse, 1983;Walton, 1982).…”
mentioning
confidence: 99%